Kapitał ludzki w kalkulacji wartości majątkowej przedsiębiorstwa - Durbajło-Mrowiec, Małgorzata (Human Capital in the Asset Value Calculation, 2007)
Human capital is an essential element of every economic activity. The investors are able to pay appropriate higher price for the enterprises which include this element. Scientists and executives of accounting discuss how to include human capital in enterprise assets. First attempts of human capita! introduction in balance sheet are a supplement of information which sets enterprise value. The calculating of enterprise asset value which includes human capital drives to very different conclusions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 112-120